2000
DOI: 10.1095/biolreprod62.3.628
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Chromosomal Abnormalities in Two-Cell Bovine In Vitro-Fertilized Embryos by Using Fluorescent In Situ Hybridization with Three Different Cloned Probes1

Abstract: The aim of this study was to assess the efficiency of fluorescent in situ hybridization (FISH) for detecting chromosomal abnormalities in in vitro-fertilized (IVF) bovine embryos as early as the 2-cell stage. Three different cloned probes were used, two derived from a unique sequence specific to the subtelomeric (D1S48) or subcentromeric regions (19C10) of chromosome 1 and the third (H1A clone) derived from a repetitive sequence that hybridizes to the subcentromeric regions of three other chromosomes (14, 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…Slimane et al [26] reported that 34.2% of two-cell IVF embryos had abnormalities such as haploidy, mixoploidy, hyperploidy and hypoploidy. Previous studies have examined pronuclear formation status and PB extrusion to judge the presumptive nucleus state [19,25,29].…”
Section: Discussionmentioning
confidence: 99%
“…Slimane et al [26] reported that 34.2% of two-cell IVF embryos had abnormalities such as haploidy, mixoploidy, hyperploidy and hypoploidy. Previous studies have examined pronuclear formation status and PB extrusion to judge the presumptive nucleus state [19,25,29].…”
Section: Discussionmentioning
confidence: 99%
“…A haploid/diploid blastocyst was observed in the SCM-CO culture group. Mixoploidy of 1n/2n is usually found in 2-cell (Slimane et al 2000) and in 4-to 32-cell embryos (Iwasaki et al 1992). It has been suggested that the 1n/2n mosaic results from the retained activity of a polar body or is a product of polyspermy (King et al 1981, Iwasaki et al 1992.…”
Section: Discussionmentioning
confidence: 99%
“…These differences include darker cytoplasm, lower density [64], more lipids, specifically, more triglycerides and less lipids from other classes [1], swollen blastomeres [81], a more fragile zona pellucida [19], differences in intercellular communication [10], and a higher incidence of chromosomal abnormalities [72,82]. All of these factors may contribute to the higher sensitivity to cryoinjury exhibited by IVP embryos.…”
Section: Differences Between In Vivo-and In Vitro-produced Embryosmentioning
confidence: 99%